Drip Irrigation Management System and Monitoring Soil Using Wireless Sensors - Shiral, Jayashree Shiral; Hazra, Monika; Thakre, Prajakta; Gawande, Ankita; Bhadang, Karishma (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
In this paper, we are using two sensors to sense the humidity and temperature of the soil .water is very precious to all human being as well as to plants. With the help of drip irrigation water will be maintained at constant level which means the water will reach to the roots drop by drop if the field is irrigated heavily with a water, there are chances that a plants may die because of unnecessary irrigation. The water could also wash them away during irrigation if very strong force of water is released at the same time. On the other hand, if there is not enough water, then also there may be chances that the plants may die due to lack of water. With the help of atomized drip irrigation system the sensor will detect the need of water by sensing the temperature & moisture and inform to the control field programmable gate array(FPGA) which will on the motor and provide water to the needed field area. Due to which the healthy plants will grow which leads to increase the productivity.